ORGANIZATION CITIZENSHIP BEHAVIOR FOR THE ENVIRONMENT AT FINANCIAL INSTITUTIONS - A.M. Nur Huda Kalimullah; Lenny Christina Nawangsari (Dinasti Publisher, 2019)
The purpose of this study is the way to understand and explain leadership and organizational culture in the Organizational Citizenship Behavior for the Environment (OCBE) by mediation through job satisfaction at financial institutions in Indonesia. The research method uses quantitative approach, which takes 125 respondents as a sample in financial institutions by questionnaire. The questioner uses Likert Scale with 5 levels of answers. The data collection thequices by questionnaires, interviews, and survey instruments whichs are sent randomly to employees at financial institutions. The data analysis is using the SEM (Structural Equation Modeling) method by the Software SmartPLS (Partial Least Square) version 3.2.8. The study revealed that leadership and organizational culture to the dimention OCBE through job satisfaction has a significant positive effect on OCBE partially and simultaneously.